2021
DOI: 10.3390/ijms22126500
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Biomarkers and Autoantibodies in Endurance Athletes: Potential Similarities with Arrhythmogenic Cardiomyopathy Pathogenic Mechanisms

Abstract: The “Extreme Exercise Hypothesis” states that when individuals perform training beyond the ideal exercise dose, a decline in the beneficial effects of physical activity occurs. This is due to significant changes in myocardial structure and function, such as hemodynamic alterations, cardiac chamber enlargement and hypertrophy, myocardial inflammation, oxidative stress, fibrosis, and conduction changes. In addition, an increased amount of circulating biomarkers of exercise-induced damage has been reported. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 162 publications
0
8
0
Order By: Relevance
“…They show variable manifestations, which render often unpredictable the prognosis definition and the anticipation of adverse events. Congenital diseases may eventually manifest during adulthood in response to specific stresses, remaining undiscovered until a dramatic or fatal episode occurs, even in agonistic athletes routinely submitted to ECG to practice [102][103][104][105][106][107][108][109][110][111]. Acquired rhythm pathologies might be induced by several causes, among which drug cardiotoxicity, cardiomyopathies, myocarditis or systemic infections, valve diseases, and interventional/surgical maldeployment of cardiac valve replacements [112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128].…”
Section: Heart Rhythm Diseases: Clinical Signs Underlying Causes and Modeling Approachesmentioning
confidence: 99%
“…They show variable manifestations, which render often unpredictable the prognosis definition and the anticipation of adverse events. Congenital diseases may eventually manifest during adulthood in response to specific stresses, remaining undiscovered until a dramatic or fatal episode occurs, even in agonistic athletes routinely submitted to ECG to practice [102][103][104][105][106][107][108][109][110][111]. Acquired rhythm pathologies might be induced by several causes, among which drug cardiotoxicity, cardiomyopathies, myocarditis or systemic infections, valve diseases, and interventional/surgical maldeployment of cardiac valve replacements [112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128].…”
Section: Heart Rhythm Diseases: Clinical Signs Underlying Causes and Modeling Approachesmentioning
confidence: 99%
“…The next challenge is to translate all the results in the field of exercise to the clinics. In particular it will be necessary to better clarify the definition of "intense/strenuous exercise" in patients, to be able to provide clear, and maybe patient-tailored, recommendation to balance between a good quality of life and the risk of sudden cardiac death (137,138).…”
Section: Role Of Exercise and Immune Response In Acmmentioning
confidence: 99%
“…Previous data showed that cardiac biomarkers such as troponins or natriuretic peptides are increased after prolonged and/or intense physical exercise, usually followed by a normalization of their serum levels within the next 24–72 h [ 86 ]. In the case of persistently elevated biomarkers in athletes, multiple mechanisms are incriminated, such as myocardial hypertrophy with subsequent fibrosis, chamber enlargement, oxidative stress or myocardial inflammation [ 87 ].…”
Section: The Soluble Tumor Necrosis Factor-like Weak Inducer Of Apoptosis Soluble Cluster Differentiation 163 and Sst2: Promising Perspecmentioning
confidence: 99%